Utilization of infrared radiation to human health - Rianti, Emillia Devi Dwi (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2013)
Infrared radiation is an electromagnetic wave, which has a wavelength between 700 nm and 1 mm. Electromagnetic wave itself has a definition, is a wave that can propagate even if there is no medium. Infrared light has a longer wavelength than visible light, but shorter than radio waves radiation. It is known that the red (from the Latin infra, "below"), red is the color of visible light with the longest wavelength. Infrared light covers 1011 Hz frequency range up to 1014 Hz or a wavelength region 10-4 cm to 10-1 cm. Today the use of infrared is widely used in the health field. Because infrared characteristics can not be seen by humans, can not penetrate opaque materials, can be caused by components that generate heat, at infrared wavelengths have the opposite relationship or inversely proportional to temperature, and when the temperature increases, the decreasing wavelength. Infrared heat produced can be used to detect health problems in organs. The purpose of this paper is, provide informationÂ  regarding the relationship between infrared rays with health.